Екологічні аспекти інтродукції рослин з позиції системного аналізу - Bulakh, P.E. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Some debatable questions of plant ecology are analyzed. The necessity of selection of independent sections of ecology is discussed. The specific methods of ecology and possibility of their use on different stages of plant introduction process are examined. The specificity of application of terminology on the theory of systems is studied, and advantages and prospects of system analysis in plant introduction are shown.